2008
DOI: 10.3801/iafss.fss.9-701
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Air Velocity on Heat Release Rate and Fire Development during Fires in Tunnels

Abstract: Model scale fire tests using wood cribs of different porosity in a ventilated tunnel are presented. The study focuses on the effect of air velocity on maximum Heat Release Rate (HRR) and fire growth rate. To study the influence of different parameters, free burn tests and fire tests inside a model-scale tunnel were performed. The tunnel was 10 m long, the widths used were 0.3 m, 0.45 m, and 0.6 m and the heights used were 0.25 m and 0.4 m. If compared to a normal traffic tunnel, these measures can correspond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Tunnels up to 700 m long, due to the traction induced by fire, have a greater probability of ventilation system collapse than longer tunnels. The fire traction in this case will increase due to the low aerodynamic resistance of the tunnel and hence the easy provision of an air supply sufficient for complete combustion (Lanchava et al, 2007;Lonnermark & Ingason, 2008). A similar opinion about fire intensification is given in (Ingason, 2010;Bajwa et al, 2009).…”
Section: Analysis Of the Statistical And Factual Data Of Tunnel Firesmentioning
confidence: 91%
“…Tunnels up to 700 m long, due to the traction induced by fire, have a greater probability of ventilation system collapse than longer tunnels. The fire traction in this case will increase due to the low aerodynamic resistance of the tunnel and hence the easy provision of an air supply sufficient for complete combustion (Lanchava et al, 2007;Lonnermark & Ingason, 2008). A similar opinion about fire intensification is given in (Ingason, 2010;Bajwa et al, 2009).…”
Section: Analysis Of the Statistical And Factual Data Of Tunnel Firesmentioning
confidence: 91%
“…The velocity of the surrounding air influences HRR, it increases sharply with an increase in the velocities of the surrounding air. In an experimental study carried out by Lönnermark and Ingason, 51 the authors tested the wood cribs in a tunnel and found that the fire growth rate increased by 5 to 10 times by increasing the surrounding air velocity three times. In the current analysis, the maximum HRR recorded for Case 1 is 1.25 times higher than Case 2, as shown in Figure 10.…”
Section: Fire Modelling Of a Compartmentmentioning
confidence: 99%
“…Moreover, Haukur Ingason et al (2008) [6] investigated the effect of air velocity on the heat release rate (HRR) and fire characteristics during a fire in the tunnel. The results showed that when increasing the ventilation rate, causing the maximum heat, the release rate increases.…”
Section: Introductionmentioning
confidence: 99%